(untitled) (SigMe, 2025)
Anderson–Fabry disease (AFD), a genetic disorder linked to the X chromosome, is caused by mutations in the gene encoding the enzyme α-galactosidase A. The resulting enzyme deficiency leads to a systemic lysosomal accumulation of alpha-galactosyl residues in glycolipids and glycoproteins. In AFD, myocardial ischemia is caused by an increased oxygen demand in the hypertrophic myocardium, which is exacerbated by reduced capillary density and small vessel compromise due to glycolipid deposits. Enzyme replacement therapy (ERT) is the treatment of choice for this form of microvascular angina. We present the case of a 60-year-old obese, hypothyroid female with a personal and family history of Fabry disease, diagnosed 20 years prior. She had discontinued her specific enzyme replacement treatment (agalsidase alfa) and was a carrier of an implantable cardioverter-defibrillator (ICD) for primary prevention. She was admitted to the Cardiology department of J. M. Cullen Hospital due to two months of oppressive, central chest pain. The pain, classified as functional class II, resolved with rest. The physical exam was unremarkable. The electrocardiogram showed no acute ischemic changes, and cardiac biomarkers were not elevated. An echocardiogram revealed severe concentric left ventricular hypertrophy with severely depressed systolic function due to diffuse global hypokinesis, as well as hypertrophy of the right ventricular free wall. A previous echocardiogram had shown preserved left ventricular systolic function. Coronary angiography did not show significant lesions in the epicardial vessels. The patient’s condition was interpreted as microvascular angina secondary to AFD. She restarted enzyme replacement therapy, and her symptoms resolved. Microvascular angina is the most frequent cause of chest pain in AFD patients due to microvascular compromise from glycolipid deposits, and enzyme replacement therapy is the most effective treatment for this condition.